Effect of Advertisment on Consumer Buying Behavior (International Journal of Scientific Research and Management (IJSRM), 2016)
Advertisement plays an important role in modern era as it shapes the attitudes and perceptions of individuals and society which strikingly influences the customer buying behaviour .Any business can get on the road of success when it attracts and retains the consumers with profit and this goal is achieved when company builds a strong consumer perception for its product or service. All the big guns have made significant attempts to ensure quality advertisement and fabrication of strong consumer perception through suitable ways that positively affects the consumer buying behavior because people get knowledge about product through advertisement and other promotional tools and develop perception through company’s activities and his previous experience with that company and past purchase accordingly